FENOMENA ADIKSI INTERNET DAN MEDIA SOSIAL PADA GENERASI XYZ - Imelda Uli Vistalina Simanjuntak; Endang Darwati; Desti Madya Saputri; Hurianti Vidyaningtyas; Sulistyaningsih Sulistyaningsih; Dimitri Mahayana (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
The phenomenon of internet and social media addiction has attracted the attention of many people. We have conducted a research to examine whether or not the phenomenon of addiction to the internet and social media is a scientific reality. Then, we follow up this research. About 2014 respondents have been surveyed. Pearson’s Product Moment and Cronbach's Alpha tests were conducted to find out whether or not all the questions on this survey questionnaire were valid and reliable. The Chi Square hypothesis test was put forward Helmert’s theory around 1960; Helmert was a German Mathematical Physicist who mainly studied the field of Geodesy, even though Ernst Abbe and Irenne Jules Bienayme had already discovered this Chi Square distribution. The results of the internet addiction survey showed that 74.68% of respondents were not addicted and the rest were addicted mildly, moderately and severely. For the social media addiction survey, 79.94% of respondents were not addicted and the rest were addicted. Variables affecting addiction are age, occupation, and education. Internet and social media addiction is mostly experienced by Generation Y and Z, while Generation X has less addiction. The results of the measurement of Internet and social media addiction include scientific reality and attention should be paid to it and steps should be taken in the context of prevention and recovery for those who are addicted. Prevention and recovery for those who are addicted can be done by involving three major components: family, community, and state.